KRYZYS CZY NOWY ETAP ROZWOJU? Z BADAŃ NAD PRZEOBRAŻENIAMI PIASTOWSKICH OŚRODKÓW GRODOWYCH W XII I XIII WIEKU – PRZYKŁADY KRUSZWICY I LĄDU NAD WARTĄ - Brzostowicz, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
The article presents the transformation of stronghold in Poland in the 12th and 13th centuries. By providing the examples of Kruszwica (Kuyavia) and Ląd (Wielkopolska), attention has been drawn to the fact that, despite the collapse of the strongholds around which gords were once organised, they could continue development and remain political, societal, religious, economic and cultural centres. They allow historians to take a different view of the operations of the then territorial and administrative organisation in Poland as well as the gradual disintegration of the system.